CEMİL KAVUKÇU'NUN HİKAYELERİNDE YAPI VE TEMA İNCELEMESİ - KARAKOÇAN, MELTEM (Fırat Üniveristesi, 2007)
Çalışmamızda, Cumhuriyet Dönemi Türk Edebiyatı'nın çağdaş yazarlarındanolan Cemil Kavukçu'nun öykülerini yapı ve tema açısından çözümlemeye çalıştıkÇalışmamızı 4 ana bölüm halinde düzenledik. Monografi nitelikli BirinciBölüm'de Cemil Kavukçu'nun yaşamı , edebi kişiliği ve yapıtlarının değerlendirmesiniyaptık.İkinci Bölümde Cemil Kavukçu'nun öykü türünde 99 yapıtındaki ortak yapıyıtespit etmeye çalıştık.Üçüncü Bölüm'de öyküleri tema bakımından incelemeye çalıştık.Eserden yolaçıkarak yazara ulaşmayı ,hedefleyen bir değerlendirme tarzını esas alarak üzerindedurulan izleklerin işleyiş biçimi üzerinde durduk.Çalışmaya,yaptığımız çözümlemeyi materyallerle tamamlama amacıyla CemilKavukçu ve alan ilgili bir kaynakça ekledik.

In this study, the stories Cemil KAVUKÇU, who is one of the neotric authors ofTurkish Literature in Republic Era, has been analysed in terms of structure and theme.This study consists of 4 chapters:The first chapter is a monographic composition and within this chapter, the life,his literary personality and works of Cemil KAVUKÇU have been evaluated.In the second chapter, I have tried to determine the items that built up thecommon structure of his 99 stories.The third chapter consists of the study of his stories analysis considering thethemes. I have aimed to arrive to the writer beginning from his stories and I haveconsidered this way in order to find out how the themes are handled.In order to end up this analysis with materials, a bibliography which consists ofCemil Kavukçu and his field has been added to the study.
The analysis of Cemil Kavukçu's stories in terms of theme and structure
Keywords: Türk Dili ve Edebiyatı